2022
DOI: 10.21037/atm-22-1438
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous microenvironment analysis to explore the potential regulatory role of endothelial-mesenchymal transition in idiopathic pulmonary fibrosis

Abstract: Background: Idiopathic pulmonary fibrosis (IPF) is a chronic and progressive interstitial lung disease mainly caused by excessive proliferation of fibroblasts and activation of myofibroblasts. The cellular microenvironment is mainly composed of different types of cellular components and extracellular matrix (ECM), whose changes directly affect cellular heterogeneity, resulting in immensely complex cellular interactions. However, microenvironment study is mainly focused on the pathological process of tumors, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The microstructure shows that ECs in the fibrotic area of PF lose their endothelial characteristics, such as polarity and intercellular junctions, while acquiring mesenchymal cell characteristics, such as a spindle-shaped cell morphology and increased migration ability [38]. In addition, the results of immunofluorescence staining and single-cell sequencing also showed that the expression of mesenchymal cell marker proteins was also observed in these ECs [39,40]. It has been reported that vascular damage occurred first in radiationinduced lung fibrosis (RIPF), including narrowing and obliterating capillaries induced by EC swelling, fibrin deposition, and endothelial hyperplasia [41].…”
Section: Endothelial-mesenchymal Transitionmentioning
confidence: 94%
“…The microstructure shows that ECs in the fibrotic area of PF lose their endothelial characteristics, such as polarity and intercellular junctions, while acquiring mesenchymal cell characteristics, such as a spindle-shaped cell morphology and increased migration ability [38]. In addition, the results of immunofluorescence staining and single-cell sequencing also showed that the expression of mesenchymal cell marker proteins was also observed in these ECs [39,40]. It has been reported that vascular damage occurred first in radiationinduced lung fibrosis (RIPF), including narrowing and obliterating capillaries induced by EC swelling, fibrin deposition, and endothelial hyperplasia [41].…”
Section: Endothelial-mesenchymal Transitionmentioning
confidence: 94%
“…52 Various fibrotic diseases, including PF, result from the abnormal activation of fibroblasts, primarily caused by the transformation of normal resident fibroblasts, as well as epithelial or endothelial cells within lung tissue. 53 Myofibroblast foci develop as a result of migration, proliferation and activation of mesenchymal cells induced by activated AECs. The excessive secretion of ECM proteins by myofibroblasts disrupts pulmonary homeostasis and structure, leading to pulmonary interstitial matrix sclerosis and pathological matrix deposition.…”
Section: Fibroblastsmentioning
confidence: 99%
“…In addition, increased expression of the myofibroblast markers N-cadherin, S100A4, and vimentin was reported in the arterial layers of IPF patients, suggesting that resident lung endothelial cells may transdifferentiate into mesenchymal/myofibroblast-like cells [ 28 ]. In a recent study employing single-cell analysis and gene expression profile data from lung tissues of IPF patients, the number of endothelial cells was found to be significantly decreased, while the number of fibroblasts and myofibroblasts significantly increased [ 29 ]. Moreover, gene expression profile in the IPF group revealed an increase in the biological processes related to fibroblast function (e.g., cellular response to fibroblast growth factor stimulation and collagen fibril organization), suggesting the occurrence of EndMT during IPF development [ 29 ].…”
Section: Direct Contribution Of Endothelial Cells To Tissue Fibrosis:...mentioning
confidence: 99%
“…In a recent study employing single-cell analysis and gene expression profile data from lung tissues of IPF patients, the number of endothelial cells was found to be significantly decreased, while the number of fibroblasts and myofibroblasts significantly increased [ 29 ]. Moreover, gene expression profile in the IPF group revealed an increase in the biological processes related to fibroblast function (e.g., cellular response to fibroblast growth factor stimulation and collagen fibril organization), suggesting the occurrence of EndMT during IPF development [ 29 ]. In another recent experimental work, endothelial-specific overexpression of sterol regulatory element-binding protein 2 (SREBP2), a protein with key role in oxidative stress-induced endothelial dysfunction, was shown to exacerbate vascular remodeling and induce pulmonary EndMT in bleomycin-treated mice [ 30 ].…”
Section: Direct Contribution Of Endothelial Cells To Tissue Fibrosis:...mentioning
confidence: 99%